Biodegradable Polymer-Based Food Packaging - Dutt Tripathi, Abhishek; Darani, Kianoush Khosravi; Rai, Dinesh Chandra; Paul, Veena (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book covers different aspects of biodegradable packaging, such as their sourcing and application in food industries. The book focuses on the production and characterization of biodegradable food packaging derived from plant, animal and microbial sources. Chapters highlight the nano-technological interventions in biodegradable food packaging and the less studied microbial biopolymer-based biodegradable food packaging makes it distinct from other related books. It includes the latest research and development in the areas of food processing, food packaging, material science and polymeric science. It also discusses the standards and regulatory guidelines about the biodegradability testing of these polymers. This book is meant for researchers in food science, food packaging, bioprocess technology, polymer science and biochemical engineering. It is also beneficial for faculty members and students of food microbiology, food technology, dairy technology. The book is also meant for small entrepreneurs and farmers who are interested in bio-plastic usage for food packaging.
Chapter 1. Introduction-Scope and importance of biodegradable polymers -- Chapter 2. Plant derived biopolymers in food packaging-current status and market potential -- Chapter 3. Plants and Animal Derived Enzymes and Their Potential Application in Food Processing and Preservation -- Chapter 4. Microbial derived biodegradable polymers as food packaging tool -- Chapter 5. Polyhdroxyalkanoates (PHAs) in Food packaging -- Chapter 6. Green polymer based biodegradable packaging -- Chapter 7. Role of agro-waste in economical food packaging synthesis -- Chapter 8. Enzymes involved in synthesis of biodegradable food packaging materials -- Chapter 9. Metabolic engineering for the synthesis of biodegradable polymers with potential applications in food packaging -- Chapter 10. Downstream processing strategies for synthesis of biodegradable polymers -- Chapter 11. Functionality test methods for biodegradable polymers -- Chapter 12. Nanocomposite biodegradable polymers for food packaging -- Chapter 13. Application of biopolymer blends as edible films and coatings in food packaging -- Chapter 14. Biopolymer based active and intelligent packaging for food applications -- Chapter 15. Standards and guidelines for testing biodegradability of bio-plastic -- Chapter 16. Future prospects of Biodegradable polymers in Food industry.
Keywords: Food science; Biotechnology; Food-Microbiology.; Biopolymers; Biomaterials; Food-Safety measures; Food Science; Biotechnology; Food Microbiology; Biopolymers; Food Safety